Admissible estimators of a multivariate normal mean vector when the scale is unknown. (17th December 2020) - Maruyama, Y; Strawderman, W E
Summary: We study admissibility of a subclass of generalized Bayes estimators of a multivariate normal vector in the case where the variance is unknown, under scaled quadratic loss. Minimaxity is established for some of these estimators.